Meningkatkan Kemampuan Literasi Membaca Melalui Kegiatan Bermain Flashcards Pada Anak Kelompok B di Taman Kanak – Kanak Dar El–Fikri Batu Merah - Sulistiyani Sulistiyani; Sulastri Sulastri; Tri Rahma Karlina Sari (LPPI Yayasan Almahmudi bin Dahlan, 2023)
Not all children have sufficient memory and ability to concentrate so that reading will feel like a heavy burden for children. This is consistent with the findings in the pre-observation in PAUD, Batam City, where children have inadequate beginning reading skills. This condition will certainly be very troubling both for the development of children and parents. This study uses a qualitative descriptive method, the activity plan will be carried out in four stages, namely (1) planning begins with conducting observations and field studies, compiling learning plans and themes, developing media according to the chosen theme, (2) implementation, namely applying flashcard media in learning which is carried out in several cycles according to the level of child development (3) observation and evaluation of the results achieved and the obstacles obtained during the activity (4) reflection on the results and obstacles obtained during the activity to take the next action to achieve the planned goals. The results showed that flashcard media can improve the ability to read beginning in group B children. this can be seen from the previous data that only 5 children who have the ability to read beginning increased to 15 children out of a total of 20 children. Keywords: pre-reading, learning media, flashcards